(untitled) (Impact: Journal of Transformation, 2024)
This study is a quantitative research investigation into the dynamic relationship between faith and mental health in the youth within an evangelical urban Christian community in Nairobi, Kenya. Through an in-depth analysis of existing literature, and data collected from structured interviews, this research sought to shed light on the ways in which faith principles and mental health practices intersect. This research explored how different theological frameworks and community structures influence attitudes towards mental health and the provision of support needed. The participants were selected through purposive sampling of individuals from the Youth Ministry of Mamlaka Hill Chapel, which is an evangelical urban Christian community located within the campus hostel grounds of the University of Nairobi, Kenya. The sample size involved 54 students drawn from a population of 400 youths who frequent the church. Key findings highlighted the importance of destigmatizing mental illnesses through education programs, and the availability of resources for individuals facing mental health challenges within Christian congregations. While this study was limited to structured interviews, the findings highlighted best practices and recommendations for promoting mental health awareness and support within faith-based settings whilst providing insight into the potential strategies for reduced stigma surrounding mental illness. By acknowledging the interconnectedness of faith and mental health, the need for collaboration between mental health professionals, clergy, and congregants is needed to provide comprehensive care that addresses both the spiritual and psychological aspects of well-being. In conclusion, the 1 Impact: Journal of Transformation Vol. 7 (2) 2024, ISSN 2617-5576 findings from this study underscore the need for targeted interventions to address mental health stigma within Christian communities and enhance support structures for individuals navigating mental health challenges. This research contributes to the ongoing dialogue on holistic well-being and the prioritizing of mental health awareness and support, and the integration of faith principles in mental health support systems